2009
DOI: 10.1038/ncb1891
|View full text |Cite
|
Sign up to set email alerts
|

Lateral microtubule bundles promote chromosome alignment during acentrosomal oocyte meiosis

Abstract: Although centrosomes serve to organize microtubules in most cell types, oocyte spindles form and mediate meiotic chromosome segregation in their absence. Here, we use high-resolution imaging of both bipolar and experimentally-generated monopolar spindles in C. elegans to reveal a surprising organization of microtubules and chromosomes within acentrosomal structures. We find that homologous chromosome pairs (bivalents) are surrounded by microtubule bundles running along their sides, whereas microtubule density … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
232
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 142 publications
(250 citation statements)
references
References 39 publications
(48 reference statements)
16
232
1
1
Order By: Relevance
“…(E) A pathway for biorientation. (Rogers et al 2002;Wignall and Villeneuve 2009). The C. elegans CPC ring is a complex structure that, as in Drosophila, contains motor proteins (Klp-19) (Powers et al 2004) and is required for segregation of homologs at meiosis I (Wignall and Villeneuve 2009;Dumont et al 2010).…”
Section: Cpc Promotes Spindle Assembly and Establishes The Spindle Axismentioning
confidence: 99%
See 2 more Smart Citations
“…(E) A pathway for biorientation. (Rogers et al 2002;Wignall and Villeneuve 2009). The C. elegans CPC ring is a complex structure that, as in Drosophila, contains motor proteins (Klp-19) (Powers et al 2004) and is required for segregation of homologs at meiosis I (Wignall and Villeneuve 2009;Dumont et al 2010).…”
Section: Cpc Promotes Spindle Assembly and Establishes The Spindle Axismentioning
confidence: 99%
“…(Rogers et al 2002;Wignall and Villeneuve 2009). The C. elegans CPC ring is a complex structure that, as in Drosophila, contains motor proteins (Klp-19) (Powers et al 2004) and is required for segregation of homologs at meiosis I (Wignall and Villeneuve 2009;Dumont et al 2010). The importance of noncentromeric CPC in a variety of organisms suggests that the unique demands of acentrosomal meiosis have resulted in a meiosis-specific CPC/central spindle localization pattern with a conserved role in spindle assembly and chromosome segregation.…”
Section: Cpc Promotes Spindle Assembly and Establishes The Spindle Axismentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the holocentric C. elegans oocytes appear to employ lateral microtubules to align chromosomes in metaphase [Wignall and Villeneuve, 2009] and segregate chromosomes independently of kinetochores [Dumont et al, 2010].…”
Section: Spindle Assembly In Acentrosomal Vertebrate Oocytesmentioning
confidence: 99%
“…A recent study showed that congression on the acentrosomal spindle is driven primarily by movement of chromosomes along laterally associated microtubule bundles during meiosis, 37 suggesting that the mechanism of chromosome congression in meiosis is different from that in mitosis. Although septin2 has been shown to regulate chromosome congression 36 and cytokinesis, 33 its precise roles in meiosis are unknown.…”
Section: Septin2 Is Modified By Sumoylation and Required For Chromosomentioning
confidence: 99%